PENERAPAN METODE ELEMEN HINGGA DALAM PEMILIHAN BAHAN PADA DESAIN PISAU MESIN PENCACAH PLASTIK - Rizqi Ilmal Yaqin; Bambang Hari Priyambodo; Angger Bagus Prasetiyo; Mega Lazuardi Umar (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2021)
Garbage is an unresolved problem where 14% of the 30% inorganic waste is plastic waste. Efforts in managing plastic waste are reducing the size of plastic waste to be managed. The plastic chopping machine is a tool used to reduce the size of plastic waste. One of the important components in a plastic chopping machine is a knife. Determining the material used for the knife is one of the steps in the knife-making process. Model simulation in material selection can be used to predict mechanically correct materials. The research that has been carried out has the aim of determining the effective material using FEM in terms of meeting the standard mechanical design characteristics of the blade design. As a result, all of the materials submitted meet the design requirements in the manufacture of knives under operating loading conditions. However, the recommended material in terms of technical mechanics in making plastic chopping blades is JIS SUP 9. This is because it has an Equivalent (Von-Mises) Stress value (27,695 x 10-2 MPa), Equivalent Elastic Strain (12,882 x 10-7 m / m), Total Deformation (17,722 x 10-10 m) and Safety Factor (15) optimal simulation results from other materials.